Early out-of-hospital non-invasive ventilation is superior to standard medical treatment in patients with acute respiratory failure: a pilot study. Issue 5 (27th September 2011) - Roessler, Markus Sören; Schmid, Dorothee Susanne; Michels, Peter; Schmid, Oliver; Jung, Klaus; Stöber, Jörg; Neumann, Peter; Quintel, Michael; Moerer, Onnen
Abstract : Objective: To assess in patients with acute respiratory failure (ARF) whether out-of-hospital (OOH) non-invasive ventilation (NIV) is feasible, safe and more effective compared with standard medical therapy (SMT). Patients and Interventions: Patients with OOH ARF were randomly assigned to receive either SMT or NIV. Measurements and Results: Fifty-one patients were enrolled, 26 of whom were randomly assigned to SMT and 25 of whom received NIV. Two patients were excluded because of protocol violations. OOH NIV was safe and effective in all patients. In the SMT group, treatment was not effective in five of 25 patients who required OOH mechanical ventilation (p=0.05). Patients in the SMT group were admitted to an intensive care unit (ICU) more frequently (n=17) (p<0.05) and for longer periods (3.7±6.4 days) (p=0.03) compared with patients in the NIV group (n=9, 1.3±2.6 days). Six patients in the SMT group required subsequent inhospital intubation and invasive ventilation during their hospital stays; only one patient in the NIV group required intubation (p=0.10). In contrast, patients in the NIV group received NIV more frequently (n=14) in hospital compared with patients in the SMT group (n=5) (p<0.01). Conclusions: OOH NIV proved to be feasible, safe and more effective for the treatment of ARF compared with SMT. OOH NIV promotes inhospital treatment with NIV and may reduce the frequency and length of ICU stays. Because the risks of OOH emergency intubation can be avoided, NIV should be the first-line treatment in OOH ARF if no contraindications are present.